Hysteresis in Exports - Giovannetti, Giorgia (IMF Working Papers; Working Paper ;, 1995)
This paper presents an empirical examination of the importance of hysteresis in international trade. An econometric model of export determination is developed where the presence of sunk costs causes discontinuous behavior and hysteresis so that individual exporters' decision to stay in or out of the market depends on the current value of the exchange rate as well as its past history. The aggregate level of exports is then determined by the proportion of exporters that stay in the market. The resulting non-linear model is estimated using data on manufacturing exports for the United States, Germany, and Japan. The paper finds strong evidence in favor of the presence of pricing-to-market and hysteresis only in the case of Japanese exports.